Metaphorical Verbalization of the Concept Fire in the Poetic Heritage of Yevhen Malaniuk (Linguostylistic Studies, 2020)
The article focuses on the terminological system of metaphor as a key device in the system of stylistic means of Yevhen Malaniuk. The author argues that verbal power and poetic looseness of the artist are realized via metaphorical constructions, which emerge as the result of the author’s creative work. The poetic language of Yevhen Malaniuk is laconic, and his stylistic devices represent the originality of the author's poetic worldview developed in the process of metaphoric modeling of the individual linguistic picture of the world. E. Malaniuk sought to embody the best qualities of the national language, choosing various linguistic means, consistent with the ideological and thematic content of the poetic works, maximizing their creative potential, preferences, and tastes, representing the richness of metaphorical devices, and accuracy in expression. The poet’s individual style manifests itself in the manner of a poem, a special way of thinking, lexical-semantic and stylistic senses, searching for original means of metaphorical verbalization of the concept fire, semantics and aesthetics of the word individualization. The study has revealed that E. Malaniuk’s metaphors are based on creative rethinking, artistic individual complication, and semantic transformation of the heritage of folk song and classical Ukrainian poetry of the XIX–XX centuries. The concept fire belongs to the basic models, figurative constants of the artist's poetic work. The author substantiates that the metaphorical verbalization of the concept fire in the creative work of E. Malaniuk embodies the biblical symbolic meaning of Godʼs punishment, after which a human is purified of all defilements and rises to a qualitatively higher level of spiritual development, so fire means suffering but at the same time it is liberation from the old, depressing; denoting the inner world of a person. The archetypal image of the fire actualizes the meanings associated with the destructive function of this phenomenon, so even a positive feeling of love is characterized as torment. Thus, the verbalization of the concept fire metaphorically refers primarily to negative experiences and emotions – sadness, hatred, suffering, insulting.
Keywords: metaphor,; concept fire,; worldview of the artist,; individualization of style.